Individualized Surgical Reconstruction of the Right Ventricle Outflow Tract in Double Outlet Right Ventricle With Mirror Image-Dextrocardia - Chen, Wangping; Iroegbu, Chukwuemeka Daniel; Xie, Xia; Zhou, Wenwu; Wu, Ming; Wu, Xun; Fan, Chengming; Borovjagin, Anton V.; Yang, Jinfu (Frontiers in Pediatrics, 2021)
Introduction: The purpose of this study was to report our experience in the surgical reconstruction of the right ventricular outflow tract in double outlet right ventricle with a major coronary artery crossing the right ventricular outflow tract in the presence of mirror image-dextrocardia. Methods: From January 2005 to December 2019, nineteen double outlet right ventricle patients (median age 4years) with mirror image-dextrocardia and a major coronary artery crossing the right ventricular outflow tract received surgical repair. An autologous pericardial patch was used to enlarge the right ventricular outflow tract in four patients without pulmonary stenosis and three patients with mild pulmonary stenosis. A valved bovine jugular venous conduit was added to a hypoplastic native pathway in nine patients, among which six patients with moderate pulmonary stenosis received small-sized bovine jugular venous conduit implantation (diameter ≤ 16mm). In comparison, a large-sized bovine jugular venous conduit (diameter >16mm) was adopted in a total of three patients with severe pulmonary stenosis. Finally, three patients with preoperative pulmonary hypertension (mean pulmonary artery pressure ≥ 40mmHg) did not undergo further intervention of right ventricular outflow tract due to the adequate outflow tract blood flow. Results: There was no hospital mortality. One patient with sub-pulmonary ventricular septal defect and concomitant severe pulmonary hypertension died from respiratory failure eleven months after the operation. Kaplan-Meier survival was 94% at 5,10years. Within a mean echocardiographic follow-up of 6.9±3.6 years, a total of two patients received reintervention due to valvular stenosis of the bovine jugular venous conduit (pressure gradient > 50mmHg at 4 and 9 years) after surgical operation. Actuarial freedom from reoperation was 90% and 72% at 5 and 10 years, respectively. During the last echocardiographic follow-up phase, all the survivors were in NYHA class I. Conclusions: Double outlet right ventricle with mirror image-dextrocardia is a rare and complicated congenital cardiac malformation. Surgical reconstruction of the right ventricular outflow tract should be individualized based on the degree of pulmonary stenosis and the specific anatomical features of each patient. Reconstructing the pulmonary artery using the various sizes of valved bovine jugular venous conduit is a safe and effective surgical method.